A Figurative Language Analysis On a Song Lyrics Found In the Night Visions (Deluxe Version) Album By Imagine Dragons - Zahira, Jihan; Wulandari, Diyah Fitri (Kajian Bahasa dan Sastra (KABASTRA), 2022)
Night Visions is Imagine Dragons’s debut album released on 4th September 2012. The aims of this study are to identify and analyze the figurative language and the contextual meaning found in the songs lyrics in Night Visions (Deluxe Version) album by Imagine Dragons. The method applied in this study is qualitative research method. The data for this study was gathered by carefully reading the song lyrics and listening to the tracks from Imagine Dragons album Night Visions (Deluxe Version). Grouping data and eliminating data are two further steps in data collection. Following the study, it was discovered that the lyrics of the song in Night Visions (Deluxe Version) album by Imagine Dragons contain a total of seven types of figurative language as well as the meaning of the figurative language. Personification, Metaphor, Hyperbole, Idiomatic Expression, Simile, Metonymy and Irony. Also by utilizing the generalized meaning for each song lyrics in Night Visions (Deluxe Version) album by Imagine Dragons, the album expresses about the struggle of the musician to build and mantain his career as a ordinary people who has recently made his musical debut. How the musician has struggled in life, and also reveals a part of himself that is rarely seen by others. Also the musicians struggle to keep his relationship with his loved ones.